NEIL1 and NEIL2 DNA glycosylases protect neural crest development against mitochondrial oxidative stress - Han, Dandan (eLife, 2019)
Base excision repair (BER) functions not only in the maintenance of genomic integrity but also in active DNA demethylation and epigenetic gene regulation. This dual role raises the question if phenotypic abnormalities resulting from deficiency of BER factors are due to DNA damage or impaired DNA demethylation. Here we investigate the bifunctional DNA glycosylases/lyases NEIL1 and NEIL2, which act in repair of oxidative lesions and in epigenetic demethylation. Neil-deficiency in Xenopus embryos and differentiating mouse embryonic stem cells (mESCs) leads to a surprisingly restricted defect in cranial neural crest cell (cNCC) development. Neil-deficiency elicits an oxidative stress-induced TP53-dependent DNA damage response, which impairs early cNCC specification. Epistasis experiments with Tdg-deficient mESCs show no involvement of epigenetic DNA demethylation. Instead, Neil-deficiency results in oxidative damage specific to mitochondrial DNA, which triggers a TP53-mediated intrinsic apoptosis. Thus, NEIL1 and NEIL2 DNA glycosylases protect mitochondrial DNA against oxidative damage during neural crest differentiation.